Structure-Function Relationship of a Gellan Family of Polysaccharide, S-198 Gum, Produced by Alcaligenes ATCC31853 - Tako, Masakuni; kitajima, Seiko; Yogi, Takuya; Uechi, Keiko; Onaga, Masayuki; Tamaki, Yukihiro; Uechi, Shuntoku (Scientific Research Publishing, 2016)
The structure-function relationship of a gellan family of polysaccharides, S-198 gum produced by Alcaligenes ATCC31853 was investigated in terms of rheological aspects. The flow curves of S-198 gum showed plastic behavior above 0.3%. Gelation did not occur in S-198 gum solution at low temperature (0℃), even at 0.8%. Both the viscosity and the elastic modulus remained constant with increasing temperature up to 80?C. The elastic modulus decreased a little with the addition of CaCl2 (6.8 mM), but then once again remained constant up to 80℃. The highest elastic modulus was observed for deacylated gellan gum with the addition of CaCl2 and increased slightly with increasing temperature up to 80℃, which was considered to be a transition temperature, after which it decreased rapidly. The elastic modulus of S-198 gum in the presence of urea (4.0 M) was lower than that in aqueous solution at low temperature (0℃), but remained constant with increasing temperature up to 80℃. The intramolecular associations, (hydrogen bonding and van der Waals forces of attraction), of S-198 gum molecules in aqueous solutions were proposed. The gellan family of polysaccharides, S-198, S-88, S-657, rhamsan, welan and gellan gum, provided a good opportunity to investigate the structure-function relationship for polysaccharides.
Keywords: S-198 Gum, Alcaligenes ATCC31853, Thermal Stability, Intramolecular Associations, Gellan Family of Polysaccharid